(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study aimed to examine and compare the speed and agility levels between athletes participating in Native and Non- Native sports. Forty male athletes were selected, comprising twenty Native Kho-Kho players and twenty Non- Native Hockey players, all of whom competed at various levels, including subdivision, district, and state competitions. The participants, aged between 14 and 16 years, were exclusively male. The analysis revealed differences in the average motor performance between the two groups. Specifically, Non- Native players exhibited lower levels of speed and agility compared to their Native counterparts. A t-test was conducted to statistically compare the motor performance between Native and Non- Native athletes, revealing no significant differences in speed (p = 0.77) or agility (p = 1.23) between the groups. Consequently, the study concluded that there were no statistically significant differences in motor performance variables between Native and Non- Native players. These findings highlight the need for future research to develop strategies to enhance motor performance in athletes from these specific populations.